New insights in lipid metabolism: potential therapeutic targets for the treatment of Alzheimer’s disease - Cao, Yuan; Zhao, Lin-Wei; Chen, Zi-Xin; Li, Shao-Hua (Frontiers in Neuroscience, 2024)
Alzheimer’s disease (AD) is increasingly recognized as being intertwined with the dysregulation of lipid metabolism. Lipids are a significant class of nutrients vital to all organisms, playing crucial roles in cellular structure, energy storage, and signaling. Alterations in the levels of various lipids in AD brains and dysregulation of lipid pathways and transportation have been implicated in AD pathogenesis. Clinically, evidence for a high-fat diet firmly links disrupted lipid metabolism to the pathogenesis and progression of AD, although contradictory findings warrant further exploration. In view of the significance of various lipids in brain physiology, the discovery of complex and diverse mechanisms that connect lipid metabolism with AD-related pathophysiology will bring new hope for patients with AD, underscoring the importance of lipid metabolism in AD pathophysiology, and promising targets for therapeutic intervention. Specifically, cholesterol, sphingolipids, and fatty acids have been shown to influence amyloid-beta (Aβ) accumulation and tau hyperphosphorylation, which are hallmarks of AD pathology. Recent studies have highlighted the potential therapeutic targets within lipid metabolism, such as enhancing apolipoprotein E lipidation, activating liver X receptors and retinoid X receptors, and modulating peroxisome proliferator-activated receptors. Ongoing clinical trials are investigating the efficacy of these strategies, including the use of ketogenic diets, statin therapy, and novel compounds like NE3107. The implications of these findings suggest that targeting lipid metabolism could offer new avenues for the treatment and management of AD. By concentrating on alterations in lipid metabolism within the central nervous system and their contribution to AD development, this review aims to shed light on novel research directions and treatment approaches for combating AD, offering hope for the development of more effective management strategies.